A Place for Space: The Shift to Online Space Education During a Global Pandemic - Roche, Joseph; Bell, Laura; Hurley, Mairéad; D’Arcy, Grace; Owens, Brendan; Jensen, Aaron M.; Jensen, Eric A.; Gonzalez, Jorge R.; Russo, Pedro (Frontiers in Environmental Science, 2021)
The COVID-19 global pandemic has transformed the relationship between science and society. The ensuing public health crisis has placed aspects of this relationship in harsh relief; perceptions of scientific credibility, risk, uncertainty, and democracy are all publicly debated in ways unforeseen before the pandemic. This unprecedented situation presents opportunities to reassess how certain disciplines contribute to the public understanding of science. Space education has long provided a lens through which people can consider the intersection of the natural world with society. Space science is critical to understanding how human activity and pollution affect global warming, which in turn, inextricably links it to perceptions of the natural world, environmental change, science communication, and public engagement. The pandemic has caused a dramatic shift in how space education projects connect with public audiences, with participation pivoting to online engagement. This transition, coupled with the renewed societal examination of trust in science, means that it is an ideal time for the field of space education to reflect on its development. Whether it evolves into its own distinct field, or remains an area that straddles disciplinary boundaries, such as science education, communication, and public engagement, are crucial considerations when scientific trust, accountability, and responsibility are in question. This paper describes the current state of space education, recent advances in the field, and relevant COVID-19 challenges. The experience of an international space education project in adapting to online engagement is recounted, and provides a perspective on potential future directions for the field.